P1804DIALYSIS AFTERKIDNEY GRAFT LOST: DATA OF THE ITALIAN REGISTRY OF PEDIATRIC DIALYSIS. (6th June 2020) - La Porta, Edoardo; Conversano, Ester; Zugna, Daniela; Consolo, Silvia; Labbadia, Raffaella; Mattozzi, Francesca; Parolin, Mattia; Verrina, Enrico Eugenio; Vidal, Enrico
Abstract: Background and Aims: An increasing number of patients are returning to dialysis after kidney allograft failure (KAF). These patients are at higher risk of complications and mortality compared with incident ESKD patients.. In the pediatric population these data are missing and outcomes have never been investigated before in a nationally representative sample. The aim of this study was to describe the characteristics and hard outcomes of children entering dialysis after KAF in a large population of pediatric dialysis patients. Method: We retrospectively reviewed the files of patients receiving chronic dialysis at < 18 years, recorded from January 1990 to June 2019 by the Italian Registry of Pediatric Chronic Dialysis (IRPCD), a nationwide population-based chronic dialysis network involving all 12 Italian pediatric dialysis centers. We identified 126 patients who had returned to dialysis after KAF. All patients were followed from (re)initiation of dialysis until death, re-transplantation or loss to follow-up. Multivariable regression and survival analysis were used to evaluate factors involved in the choice of dialysis modality and patient outcomes. Results: After KAF, 45 (35.7 %) patients were treated with PD and 81 (64, 3%) with HD. Prior to kidney transplantation (Ktx), 74 (58.7%) were on PD, 45 (35.7%) on HD, and 7 on conservative care (5.5%). Compared with PD patients, those on HD were older (median age of 14.8 years [IQR 11.4-17.5] vs. 10.8 [IQR 2-6.5] vs.; p=0.002), had a longer transplant vintage ([55.2 months [13.2-100.3]) vs. 33 [5.1-82.2], and reentered dialysis in more recent calendar years (2013 [2007-2017] vs. 2004 [2001-2009]). Significant predictors for being treated with PD after KAF were a younger age at dialysis start (OR 0.83 per year increase [95%CI 0.72-0.94]) and a history of PD use before Ktx (OR 12.74 [2.2-74.6]). Patients returning to dialysis in more recent eras (OR 0.87 per year increase [0.81-0.94]) and those who were treated with more than one dialysis modality before Ktx (OR 0.15 for being treated with PD [0.04-0.63]) were more likely to be initiated on HD. Over the observation period, 6 PD (13.6%) and 3 HD (4.2%) patients died. After adjustment for several covariates, patients on PD exhibited an increased risk for mortality compared with HD (HR 4.65 [1.12-19.30], while the difference for modality failure and access to renal transplantation did not reach statistical significance (Fig.1) Conclusion: Patients returning to dialysis after KAF in more recent years are more likely to be initiated on HD rather than PD. According to our registry data, the use of PD is associated with a lower survival among patients initiating dialysis after KAF.